Inhibitory effects of Kampo medicines, Keishibukuryogan and Shakuyakukanzoto, on the substrate uptake activities of solute carrier organic anion transporters - Ho-Sung Lee; Ho Jung Shin; Munju Cho; Seung Hoon Lee; Dal-Seok Oh (Elsevier, 2018)
The aim of this study was to assess the effects of Keishibukuryogan (K-06) and Shakuyakukanzoto (TJ-68), commercial herbal medicines, on the substrate uptake activities of renal organic anion transporters. We performed transporter uptake and cell viability assays in Xenopus oocytes and HEK293 human kidney embryonic cells treated with K-06 or TJ-68. K-06 and TJ-68 markedly inhibited the substrate uptake activities of URAT1, OAT1, and OAT3, while they did not exhibit non-cytotoxic effects. Our findings demonstrated that K-06 and TJ-68 inhibited the substrate uptake activities of renal transporters, suggesting their mechanism of action as nephroprotective agents.